Analysis of Concept Construction and Scale Development of Employee Zhengchong Behaviour in Family Firms in Jiangsu Province of China - Ma Z; Fan M; Ouyang C; Su J; Wu M (Psychology Research and Behavior Management, 2022)
Zejun Ma,1 Ming Fan,1 Chenhui Ouyang,1 Jialu Su,1 Mengyun Wu2 1School of Management, Jiangsu University, Zhenjiang, People’s Republic of China; 2School of Finance & Economics, Jiangsu University, Zhenjiang, People’s Republic of ChinaCorrespondence: Mengyun Wu, Tel +86 15905288730, Email mewu@ujs.edu.cnPurpose: Some scholars have explored the connotation and structural elements of employee zhengchong behaviour based on Taiwan’s local enterprises, providing results with reference significance. However, there is a lack of accurate measurement scales. How to treat employee zhengchong behaviour (striving for a favour) and effectively deconstruct it is very important to the sustainable development of family firms.Methods: Semistructured interviews were conducted with 62 employees of private enterprises, and the structural dimension of employee zhengchong behaviour was explored with the help of grounded theory. The researchers designed two questionnaires, collected 278 and 331 valid questionnaires in the two surveys, compiled the corresponding measurement scale, and tested it.Results: Employee zhengchong behaviour under differential leadership was a multidimensional structure with rich connotations consisting of four dimensions: showing abilities, collaborating and sharing, excluding outsiders, and ingratiating upwards. The scale includes 16 items.Conclusion: This study enriches the relevant theories while providing a decision reference for family firm leaders to guide employee zhengchong behaviour to reasonably improve firm performance.Keywords: family firms, differential leadership, grounded theory, scale development